2020
DOI: 10.7759/cureus.6752
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based Training Curriculum for the Management of Vaginal Cuff Dehiscence and Evisceration

Abstract: Vaginal cuff dehiscence with evisceration (VCDE) is a serious, life-threatening complication of hysterectomy. Due to the high volume of hysterectomies performed in the U.S each year, it is likely that a practitioner will encounter VCDE during their career. Due to its infrequent occurrence, residents receive little exposure to it during training. Delayed diagnosis of VCDE can impede proper management and lead to severe, long-term complications or death. Our goal was to provide an opportunity for resident physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Others did not find a significant influence of surgeon volume [ 12 , 19 ]. Chapman et al [ 40 ] organized a simulation for recognition and management of VCD, and found gynecology residents’ knowledge and confidence in recognizing VCD, identifying the need for surgical management, and performing a reduction of prolapsed bowel and vaginal cuff repair to be improved after the training.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Others did not find a significant influence of surgeon volume [ 12 , 19 ]. Chapman et al [ 40 ] organized a simulation for recognition and management of VCD, and found gynecology residents’ knowledge and confidence in recognizing VCD, identifying the need for surgical management, and performing a reduction of prolapsed bowel and vaginal cuff repair to be improved after the training.…”
Section: Review Of the Literaturementioning
confidence: 99%